ANALISIS PERAN ASEAN REGIONAL FORUM DALAM PENYELESAIAN SENGKETA LAUT CHINA SELATAN - Sitompul, Melda Alani (Universitas Panca Marga, 2022)
The ASEAN Regional Forum (ARF) is a forum established by ASEAN countries to maintain regional security and prevent security instability in the region. The role of the ARF is to agree on a “DOC Implementation Manual” which aims to defuse tensions and promote the peaceful management of situations and respect for the status quo. Ongoing discussions and dialogues within ASEAN as well as ASEAN and China regarding the implementation of the DOC through the Code of Conduct (COC) for South China Sea disputes. Thus ASEAN plays a very important role. This role is interesting to study in the implementation of DOC through COC in ARF. This paper wants to examine this role using a descriptive qualitative approach using secondary sources through supporting and relevant news, documentation, and journals. Keywords: role, asean regional forum, maritime boundary disputes, code of conduct, south china sea, declaration on the conduct